Predicting the Distribution of Sunda Pangolin (Manis javanica Desmarest, 1822) in Way Canguk Research Station, Bukit Barisan Selatan National Park, Lampung - Silvi Dwi Anasari; Wulan Pusparini; Noviar Andayani (Universitas Gadjah Mada, 2021)
The distribution of a species can help guide the protection activities in their natural habitat. Conversely, the lack of information on this distribution makes the protection strategy of this species difficult. The research was conducted in Way Canguk Research Station, Bukit Barisan Selatan National Park from January until March 2018. The purposes of this research were to create a distribution prediction map of Sunda pangolin (Manis javanica) and estimating the environment variables that most influenced the probability of the distribution. Fourteen points of camera trap coordinates were used for presence data with nine types of environment variables such as elevation, slope, understorey, canopy cover, distance from roads, distance from rivers, distance from villages, food source, and distance from the threat. The result of maxent showed an Area Under the Curve (AUC) value of 0.909 categorized as very good. The highest probability of Sunda pangolin distributions was in the Pemerihan Resort and Way Haru Resort area, while the dominant environmental variables included the distance from the village, the canopy cover, and the distance from threat with the value 47.7; 25.85; and 15.8%, respectively. Prediction maps and environment variables can help to identify the population of Sunda pangolin in the wild and can provide input for the national parks to prioritize protection areas for Sunda pangolin from the increased poaching.